FACTORS RELATED TO THE INCIDENCE OF HYPERTENSION IN NON-MEDICAL WORKERS AT X BOGOR HOSPITAL - Eriskadevi, Evri; Mugi Wahidin; Ade Heryana; Susi Shorayasari (Indonesia Epidemiological Journal, 2023)
Background: Hypertension is a degenerative disease that is a severe problem in the world. Hypertension is categorized as a silent killer disease because sufferers do not know they have hypertension. According to the World Health Organization (2021), 42% of sufferers are unaware of having hypertension because it often occurs without complaints. Purpose: The purpose of this study was to determine whether there is a relationship between age, gender, family history, smoking habits, and obesity with the incidence of hypertension. Methods: The type of research conducted was quantitative with a cross-sectional approach. The sample size obtained from the results of the study was 58 samples. The research took place in April - July 2023. The instruments used in this study were questionnaires and digital tensimeters to measure blood pressure. The data results are presented in the form of univariate and bivariate analysis using the chi-square test. Results: The results showed that age (p=0.047), gender (p=0.015), family history (p=0.007), and obesity (p=0.019) showed a significant relationship with the incidence of hypertension. However, smoking habit (p=0.634) did not establish a significant relationship. Conclusion: age, gender, family history, and obesity showed a significant relationship with the incidence of hypertension, and smoking habit did not establish a significant relationship with the incidence of hypertension.